Permanent‐magnet energy spectrometer for electron beams from radiotherapy accelerators. Issue 9 (26th August 2015) - McLaughlin, David J.; Hogstrom, Kenneth R.; Carver, Robert L.; Gibbons, John P.; Shikhaliev, Polad M.; Matthews, Kenneth L.; Clarke, Taylor; Henderson, Alexander; Liang, Edison P.
Abstract : Purpose: The purpose of this work was to adapt a lightweight, permanent magnet electron energy spectrometer for the measurement of energy spectra of therapeutic electron beams. Methods: An irradiation geometry and measurement technique were developed for an approximately 0.54‐T, permanent dipole magnet spectrometer to produce suitable latent images on computed radiography (CR) phosphor strips. Dual‐pinhole electron collimators created a 0.318‐cm diameter, approximately parallel beam incident on the spectrometer and an appropriate dose rate at the image plane (CR strip location). X‐ray background in the latent image, reduced by a 7.62‐cm thick lead block between the pinhole collimators, was removed using a fitting technique. Theoretical energy‐dependent detector response functions (DRFs) were used in an iterative technique to transform CR strip net mean dose profiles into energy spectra on central axis at the entrance to the spectrometer. These spectra were transformed to spectra at 95‐cm source to collimator distance (SCD) by correcting for the energy dependence of electron scatter. The spectrometer was calibrated by comparing peak mean positions in the net mean dose profiles, initially to peak mean energies determined from the practical range of central‐axis percent depth‐dose (%DD) curves, and then to peak mean energies that accounted for how the collimation modified the energy spectra (recalibration). The utility of the spectrometer was demonstrated by measuring the energy spectra for the seven electron beams (7–20 MeV) of an Elekta Infinity radiotherapy accelerator. Results: Plots of DRF illustrated their dependence on energy and position in the imaging plane. Approximately 15 iterations solved for the energy spectra at the spectrometer entrance from the measured net mean dose profiles. Transforming those spectra into ones at 95‐cm SCD increased the low energy tail of the spectra, while correspondingly decreasing the peaks and shifting them to slightly lower energies. Energy calibration plots of peak mean energy versus peak mean position of the net mean dose profiles for each of the seven electron beams followed the shape predicted by the Lorentz force law for a uniform z ‐component of the magnetic field, validating its being modeled as uniform (0.542 ± 0.027 T). Measured Elekta energy spectra and their peak mean energies correlated with the 0.5‐cm (7–13 MeV) and the 1.0‐cm (13–20 MeV) R 90 spacings of the %DD curves. The full‐width‐half‐maximum of the energy spectra decreased with decreasing peak mean energy with the exception of the 9‐MeV beam, which was anomalously wide. Similarly, R 80–20 decreased linearly with peak mean energy with the exception of the 9 MeV beam. Both were attributed to suboptimal tuning of the high power phase shifter for the recycled radiofrequency power reentering the traveling wave accelerator. Conclusions: The apparatus and analysis techniques of the authors demonstrated that an inexpensive, lightweight, permanent magnet electron energy spectrometer can be used for measuring the electron energy distributions of therapeutic electron beams (6–20 MeV). The primary goal of future work is to develop a real‐time spectrometer by incorporating a real‐time imager, which has potential applications such as beam matching, ongoing beam tune maintenance, and measuring spectra for input into Monte Carlo beam calculations.